2013
DOI: 10.1007/s00106-013-2704-5
|View full text |Cite
|
Sign up to set email alerts
|

Seromukotympanon

Abstract: Using NHS, OME can be diagnosed and treated early, thus, preventing potential problems in the linguistic, social and intellectual development of children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…4% of children with conspicuous follow-up in the newborn hearing screening had unilateral serous otitis media (SOM) and 12% had bilateral SOM shortly after birth. In this group, an additional 9% had sensorineural hearing loss, which was detected after insertion of a grommet [ 28 ].…”
Section: Diagnostics and Causes Of Early Childhood Hearing Disordermentioning
confidence: 99%
See 3 more Smart Citations
“…4% of children with conspicuous follow-up in the newborn hearing screening had unilateral serous otitis media (SOM) and 12% had bilateral SOM shortly after birth. In this group, an additional 9% had sensorineural hearing loss, which was detected after insertion of a grommet [ 28 ].…”
Section: Diagnostics and Causes Of Early Childhood Hearing Disordermentioning
confidence: 99%
“…4% have a unilateral and 12% bilateral build-up of serous or mucous fluid or residual amniotic fluid in the middle ear. In nearly half of the affected infants, the OME persisted for 3 months and surgical repair of the middle ear was indicated [ 28 ]. Patients with risk factors require further procedures to repair the middle ear over the next 6 months.…”
Section: Diagnostics and Causes Of Early Childhood Hearing Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…At present, the surgical treatment timing for these infants mostly adheres to this guideline, with an operation rate of about 50 per cent. 5 One study even suggested that a diagnostic microscopic examination with myringotomy, with or without placement of a ventilation tube, should be performed. 6 As a leading institution for the treatment of children with ENT diseases in Wuhan, China, we provide clinical services for a large number of children with OME.…”
Section: Introductionmentioning
confidence: 99%